Analisis Komparatif Pendapatan Petani Kopi Organik dan Petani Kopi Anorganik di Dataran Tinggi Gayo Nanggroe Aceh Darussalam - Azhar A. Gani (Politeknik Negeri Lampung, 2008)
Organic coffee is a certain type of coffee produced by using an ecological way which is very economical. It has high quality and free or synthetic chemical substances. In other hands, Unorganic coffee is the coffee produced by using a non ecological way. It has lower quality and chemical substances are used in the cultivation so that it is not completely safe to consume. The objective of this research is to find out the difference on the incomes of the organic and unorganic coffee farmers dwelled the plateau in Gayo, Bener Meriah district, Nanggroe Aceh Darussalam. The method used in this research is a survey method. The sample is determined by using a two stage cluster sampling method with 30 organic coffee farmers and 25 organic and unorganic coffee farmers as the participants. TheÂ